Two new land planarian species (Platyhelminthes: Tricladida: Geoplanidae) from protected areas in southern Brazil - Boll, Piter Kehoma; Do Amaral, Silvana Vargas; Leal-Zanchet, Ana Maria (Zootaxa, 2019)
We describe two new species of Neotropical land planarians found in protected areas of the Atlantic Forest in southern Brazil. Cratera obsidiana Amaral, Boll & Leal-Zanchet, sp. nov., found in the State Park of Turvo, is the first species of the genus Cratera described from an area of deciduous seasonal forest. It can be distinguished from its congeners by the uniformly black dorsal color and the prostatic vesicle with proximal portion laterally expanded and directed upward. Luteostriata subtilis Boll, Amaral & Leal-Zanchet, sp. nov., found in the National Park of Aparados da Serra, in an area covered by Araucaria moist forest, is distinguished from its congeners by only two conspicuous longitudinal stripes on the dorsal surface of the body and a large fold in the male atrium below the opening of the ejaculatory duct. We also provide an updated key for species of Cratera and the first key for species of Luteostriata.